The Effects of Familial Social Support Relationships on Identity Meaning in Older Adults: A Longitudinal Investigation - Toyoshima, Aya; Nakahara, Jun (Frontiers in Psychology, 2021)
This study aimed to examine whether social support promotes identity meaning among older adults. We hypothesized that when two spouses exchange social support, their sense of marital identity is enhanced. Among older adults, parental identity may be more strongly enhanced when parents provide social support to their children rather than receive social support from them. We conducted a longitudinal survey of 355 older adults (240 men and 115 women aged >60 years), who were assessed four times over two years. First, we confirmed the relationship between social support and identity meaning using an autoregressive path model. Second, we examined the effect of social support on the trajectory of role identities in a growth curve model. The intercepts of receiving support and providing support were significantly associated with the intercept of marital identity. In addition, the intercept of identity meaning for parents correlated with the intercept of providing support to their children but not with that of receiving support from their children. Social support between family members promotes role identities in family relationships. In particular, providing support to children correlates with parental roles which connect to subjective well-being.